2007
DOI: 10.1179/174367607x156061
|View full text |Cite
|
Sign up to set email alerts
|

Coating methods for self-cleaning thick films of titania

Abstract: The present work provides a brief but wide ranging survey of the different methods that may be used to apply thick films of titanium dioxide for self-cleaning building materials. This survey is preceded by a general description of the photocatalytic applications of TiO 2 , a tabulated list of some relevant properties of the three naturally occurring polymorphs of TiO 2 and a tabulated survey of world market shares and resources of TiO 2 . The survey of coating technologies consists of succinct coverage of twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…14 Likewise, there is interest in devising "selfcleaning" coatings for reducing both indoor and outdoor air pollution. 11,15 We show that uptake of atmospheric NH 3 onto surfaces containing TiO 2 is not a permanent removal process, as previously thought, but rather a photochemical route for generating reactive oxides of nitrogen that play a role in air pollution and are associated with significant health effects. 16,17 Nitrogen oxides, such as NO and NO 2 , are byproducts of combustion and precursors of ozone, nitric acid, and secondary organic aerosol.…”
Section: ■ Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…14 Likewise, there is interest in devising "selfcleaning" coatings for reducing both indoor and outdoor air pollution. 11,15 We show that uptake of atmospheric NH 3 onto surfaces containing TiO 2 is not a permanent removal process, as previously thought, but rather a photochemical route for generating reactive oxides of nitrogen that play a role in air pollution and are associated with significant health effects. 16,17 Nitrogen oxides, such as NO and NO 2 , are byproducts of combustion and precursors of ozone, nitric acid, and secondary organic aerosol.…”
Section: ■ Introductionmentioning
confidence: 51%
“…In rural areas there has been interest in using TiO 2 -based photocatalytic devices to mitigate air emissions of odorous volatile organic compounds, hydrogen sulfide, and NH 3 from concentrated animal feed operations . Likewise, there is interest in devising “self-cleaning” coatings for reducing both indoor and outdoor air pollution. , We show that uptake of atmospheric NH 3 onto surfaces containing TiO 2 is not a permanent removal process, as previously thought, but rather a photochemical route for generating reactive oxides of nitrogen that play a role in air pollution and are associated with significant health effects. , …”
Section: Introductionmentioning
confidence: 68%
“…Previous studies reported that particles accelerated in the AD process collide with the substrate or the deposited coating layer, instantaneously releasing thermal energy [16,24]. In this way, the kinetic energy of the accelerated particles is converted into impact energy by colliding with the substrate and the formed coating layer.…”
Section: Resultsmentioning
confidence: 99%
“…The resultant coating layer is highly dense without the need for additional heat treatment, and possesses uniform and adequate adhesion between the substrate and the coating layer [11,15]. The advantages of using the AD method in this manner have led many researchers to focus on various ceramic materials such as Al 2 O 3 , Y 2 O 3 , lead zirconate titanate (PZT), or BaTiO 3 for plasma resistance or electrical properties [5,[11][12][13][14][15][16][17]. However, few studies investigated the use of glass powders with the AD method.…”
Section: Introductionmentioning
confidence: 99%
“…International Journal of Photoenergy paints for self-cleansing and microbial destruction [6], and Abdullah et al reported on the advantages and disadvantages of coating methods (dip coating, splatter coating, static brush coating, etc.) for various TiO 2 for self-cleaning applications [7]. Other popular applications include the incorporation of photocatalytic semiconductor particles in textiles.…”
Section: Introductionmentioning
confidence: 99%